PENTINGNYA IDENTIFIKASI PATAHAN AKTIF DALAM UPAYA MITIGASI BENCANA DI KAWASAN PENDIDIKAN JATINANGOR, JAWA BARAT - Muslim, Dicky; Endyana, Cipta (Bulletin of Scientific Contribution, 2015)
West Java region is tectonically active area because it is close to the subduction zone between the Eurasian continental plate with the Indo-Australian oceanic plate. This led to the high intensity of the presence of active faults, either already identified or not. Jatinangor areas as education city is now growing very rapidly filled by a variety of campus facilities. There are four major colleges (UNPAD, ITB, IKOPIN, STPDN) and various supporting infrastructure. With the increasing number of population and limited land can be built, the various geological resources in this area should be managed as well as possible, including land resources as part of the various geological resource potential that can be developed to meet the needs and desires of humans. The existence of various lineament of morphology around the area Jatinangor considered as a continuation of the path which uncategorized Lembang Fault is active. A number of earthquake ever recorded in the past has the epicenter around this fault. This study aims to explain the importance of the identification of active faults in disaster mitigation efforts on the limited land resources but must meet the needs of the growing population. The results showed that there are a number of alignment around G. Manglayang that can be associated with kemenrusan Lembang Fault. At the southern foot of Mt. Manglayang spread a general lineament trending north-south and northwest-southeast which is straightness lembahan and hills. In geomorphological generally show the characteristics of active faults that are vulnerable to earthquake activity. This will limit the different characteristics of land that can be built because it must take into account the values of dynamic bearing capacity as the earthquake disaster mitigation efforts in the future. In addition, it is also necessary mitigation efforts related to disaster education to all stakeholders in the area of research.